N-Heterocyclic Carbene (NHC)-Catalyzed One-Pot Aerobic Oxidative Synthesis of 2-Substituted Benzo[d]oxazoles, Benzo[d]thiazoles and 1,2-Disubstituted Benzo[d]imidazoles - Zhou, Quan; Liu, Shu; Ma, Ming; Cui, He-Zhen; Hong, Xi; Huang, Shuang; Zhang, Jing-Fan; Hou, Xiu-Feng (Synthesis, 2018)
N-Heterocyclic carbene (NHC), generated in situ from easily available N-heterocyclic imidazolium salt with air as terminal oxidant, has successfully been utilized as a cheap and efficient catalyst for one-pot aerobic oxidative synthesis of 2-arylbenzo[d]oxazoles, 2-substituted benzo[d]thiazoles, and 1,2-disubstituted benzo[d]imidazoles.
Keywords: N-heterocyclic carbene; organocatalysis; aerobic oxidation; cyclization; benzazoles